African traditional religion - Lugira, Aloysius Muzzanganda (New York : Chelsea House Publishers, 2009)
Explores the many manifestations of African religious belief and their expressions, in the past and in the present, as well as the hopes for the future.
Introduction: Africa and its people -- The beginning of time: the oral tradition -- The supreme being -- The spirit world -- Rites and ritual in African religion -- Sacred spaces and places -- Mystical forces -- African religion in today's world -- African religion past, present, and future.
Chelsea House and Facts on File are both imprints of Infobase Publishing.
Includes bibliographical references (p. 134-135) and index.
Keywords: Africa -- Religion -- Juvenile literature; Africa -- Religious life and customs -- Juvenile literature; Africa -- Religion; Africa -- Religious life and customs